Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1097/qad.0b013e328340fdaf
|View full text |Cite
|
Sign up to set email alerts
|

Multiple independent lineages of HIV-1 persist in breast milk and plasma

Abstract: Design-The origin and evolution of HIV-1 in breast milk is unclear, despite the continuing significance of this tissue as a transmitting compartment. To elucidate the evolutionary trajectory of viral populations in a transient mucosal compartment, longitudinal sequences of the envelope gp120 region from plasma and breast milk spanning the first year after delivery were analyzed in six women infected by HIV-1 subtype C.Methods-Multiple phylogenetic algorithms were used to elucidate the evolutionary history and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 69 publications
3
25
0
Order By: Relevance
“…Interestingly, this viral restriction is quantitative not qualitative. The HIV variants that enter breast milk are genetically indistinguishable from those in contemporaneous plasma (36,(42)(43)(44). Within breast milk, there is limited viral evolution, which may reflect restricted replication (36,43,45).…”
Section: Breast Milk Transmissionmentioning
confidence: 99%
“…Interestingly, this viral restriction is quantitative not qualitative. The HIV variants that enter breast milk are genetically indistinguishable from those in contemporaneous plasma (36,(42)(43)(44). Within breast milk, there is limited viral evolution, which may reflect restricted replication (36,43,45).…”
Section: Breast Milk Transmissionmentioning
confidence: 99%
“…Recent studies indicate that the viruses in breast milk and blood are intermingled and are not generally compartmentalized (15,17), suggesting that breast milk viruses are typical of circulating viruses. Moreover, the probability of infection per exposure during breastfeeding, measured either as per liter of breast milk ingested or by daily exposure, is generally similar to the probability of infection from one unprotected exposure during sexual transmission (38).…”
mentioning
confidence: 99%
“…The main results from these studies showed a correlation between the intrahost evolutionary rate disease progression, linear or inverse . The founding of supported monophyletic clades including sequences isolated from a specific tissue supported the existence of diverse HIV‐1 subpopulations infecting different body tissues …”
Section: Phylogenesis and Phylodynamic Of Human Immunodeficiency Virusmentioning
confidence: 74%
“…169,170 The founding of supported monophyletic clades including sequences isolated from a specific tissue supported the existence of diverse HIV-1 subpopulations infecting different body tissues. 171,172 The comparison of HIV-1 intrahost genealogies from patients sampled under different conditions could help in understanding the viral reservoir dynamics, the most important knowledge for the HIV- Phylogenetic reconstruction suggests several separate introductions of the Asian genotype (ECSA) strain, in contrast to a unique introduction of the ECSA genotype followed by virus dissemination inside the country 174,175 also in DENV outbreaks. 176 In CHIKV Italian outbreak in September 2017, phylodynamic analysis showed that the virus was in loco at least 3 months before the outbreak and, in particular, it probably originated in Pakistan and not India as the classical epidemiology supposed.…”
Section: The Phylogeny Of Genotypes B and Cmentioning
confidence: 99%